circRNA_17725 Promotes Macrophage Polarization towards M2 by Targeting FAM46C to Alleviate Arthritis - Yang, Chunjuan; Ni, Biao; Li, Chaoran; Sun, Wenchang; Wang, Zhangxue; Wang, Hui; Hou, Xinyue; Yan, Shushan; Wang, Xiaodong; Xu, Donghua (Mediators of Inflammation, 2023)
Accumulating studies have implicated that circular RNAs (circRNAs) play vital roles in the pathogenesis of rheumatoid arthritis (RA). Dysregulation of macrophage polarization leads to immune homeostatic imbalance in RA. However, the altering effects and mechanisms of circRNAs on macrophages polarization and immune homeostatic balance remain largely unclear. We aimed to investigate the potential role of circRNA_17725 in RA. The high-throughput sequence was performed to identify the dysregulated circRNAs in RA. We confirmed the data by CCK-8, EdU, and Annexin V/PI staining to elucidate the proliferation and apoptosis. The expressions of M1/M2-associated markers were confirmed using real-time PCR and flow cytometry analysis. Luciferase reporter assay and RNA Binding Protein Immunoprecipitation (RIP) were used to demonstrate the underlying mechanism of circRNA_17725. The altering effect of circRNA_17725 on macrophages in vivo was evaluated using collagen-induced arthritis (CIA) mouse model. circRNA_17725 was demonstrated to be downregulated in peripheral blood mononuclear cells and CD14+ monocytes from RA cases in contrast to healthy controls. The negative association between circRNA_17725 and the disease activity indexes (CRP, ESR, and DAS28) was observed, suggesting a vital role of circRNA_17725 in RA disease activity. Besides, after a coexpression analysis based on high-input sequencing and the bioinformatics analysis in MiRanda and TargetScan databases, a circRNA_17725-miR-4668-5p-FAM46C competing endogenous RNA (ceRNA) network was hypothesized. A series of cytology experiments in vitro have implicated that circRNA_17725 could inhibit the proliferation but enhance the apoptosis of macrophages. Decreased expression of TNF-α, IL-1β, and MMP-9 were observed in the supernatant of circRNA_17725-overexpressed Raw264.7 macrophages, implicating the inhibitory effect of circRNA_17725 on macrophage inflammatory mediators. Furthermore, circRNA_17725 could promote macrophage polarization towards M2 by targeting miR-4668-5p/FAM46C as a miRNA sponge. Additionally, circRNA_17725-overexpressed macrophages alleviated arthritis and protected against joint injuries and bone destruction by inducing macrophage polarization towards M2 in collagen-induced arthritis (CIA) mice. This study has suggested that circRNA_17725 regulated macrophage proliferation, apoptosis, inflammation, and polarization by sponging miR-4668-5p and upregulating FAM46C in RA.